Scaling a Community-Wide Campaign Intervention to Manage Hypertension and Weight Loss - Reininger, Belinda M.; Mitchell-Bennett, Lisa A.; Lee, MinJae; Yeh, Paul G.; Davé, Amanda C.; Park, Soo Kyung; Xu, Tianlin; Ochoa-Del Toro, Alma G. (Frontiers in Medicine, 2021)
Public health impacts can be achieved when evidence-based interventions are implemented to those most in need. Too often implementation never or slowly occurs. The community-wide campaign intervention Tu Salud ¡Si Cuenta! has evidence of improving health outcomes related to chronic disease among low-income, Latinos. Using the RE-AIM Framework, this study examined if the scaled-up version of the intervention is associated with improvements in hypertension and obesity in 12 locations. Each element of the RE-AIM framework was examined. For “Effectiveness”, we examined outcomes overall and by implementing location. We used linear and logistic regression to assess if exposure in the intervention was associated with improvement in hypertension and weight loss. Participants were stratified into “low exposure” (2-3 outreach visits) vs. “high exposure” (4-5 outreach visits). Based on the RE-AIM Framework, the intervention “reached” its intended population of low-income Latinos, demonstrated “effectiveness” in improving hypertension and obesity, was “adopted” at a high level in all but one site, was “implemented” with fidelity to the intervention model with moderate success across locations, and showed high “maintenance” over time. For effectiveness specifically, we found that out of 5019 participants, 2508 (50%) had a baseline hypertensive blood pressure (BP) reading. Of the 2508, 1245 (49.9%) recovered to normal blood pressure or pre-hypertension stage by last follow-up. After adjusting for baseline BP and potential confounders in multivariable linear regression models, the high exposure group had significantly more reduction in systolic BP (adjusted mean difference in % change = -0.96; p=0.002) and diastolic BP (adjusted mean difference in % change = -1.61; p<0.0001) compared to the low exposure group. After controlling for baseline weight and other confounders, the high exposure group had significantly greater decrease in weight compared to the low exposure group (adjusted mean difference in % change = -1.28; p<0.0001). Results from the multivariable logistic regression models indicated that compared to the low exposure group the high exposure group was more likely to achieve a clinically significant minimum 5% weight loss (adjusted odds ratio (OR)=2.97; p<0.0001). This study contributes evidence that a Community-Wide Campaign model holds promise for addressing hypertension and obesity among low-income Latinos.